2021
DOI: 10.1186/s13021-021-00187-2
|View full text |Cite
|
Sign up to set email alerts
|

Projected soil organic carbon loss in response to climate warming and soil water content in a loess watershed

Abstract: Background Soil organic carbon (SOC) plays a crucial role in the global carbon cycle and terrestrial ecosystem functions. It is widely known that climate change and soil water content (SWC) could influence the SOC dynamics; however, there are still debates about how climate change, especially climate warming, and SWC impact SOC. We investigated the spatiotemporal changes in SOC and its responses to climate warming and root-zone SWC change using the coupled hydro-biogeochemical model (SWAT-DayCe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Changes in atmospheric temperature could, directly and indirectly, influence the fate of soil organic carbon by regulating soil microbial growth and activity, litterfall, root death, and soil moisture (e.g., Qi et al, 2016;Yan et al, 2017;Hartley et al, 2021). Several studies have explored the effects of climate warming on soil organic carbon in forests over several decades (Kasischeke et al, 1995;Melillo et al, 2011;Zhao et al, 2021;Nottingham et al, 2022). However, there is still no scientific consensus on whether soil organic carbon decreased or increased in forests under climate warming due to the contradictory results under different experimental and numerical conditions (Kirschbaum, 2006;Bao et al, 2016;Kong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in atmospheric temperature could, directly and indirectly, influence the fate of soil organic carbon by regulating soil microbial growth and activity, litterfall, root death, and soil moisture (e.g., Qi et al, 2016;Yan et al, 2017;Hartley et al, 2021). Several studies have explored the effects of climate warming on soil organic carbon in forests over several decades (Kasischeke et al, 1995;Melillo et al, 2011;Zhao et al, 2021;Nottingham et al, 2022). However, there is still no scientific consensus on whether soil organic carbon decreased or increased in forests under climate warming due to the contradictory results under different experimental and numerical conditions (Kirschbaum, 2006;Bao et al, 2016;Kong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As the afforestation period in Guizhou is relatively short, the DOM inputs in some dead wood and litter DOM pools, such as the BG fast DOM and AG very fast DOM pools, obtained from the newly grown forest were less than the DOM decomposed, resulting in decreases in C stocks. In terms of SOM pools, including the BG very fast DOM and BG slow DOM pools, the C stock changes in response to climatic warming depend on how C inputs to soil by NPP and C outputs by SOM decomposition are balanced relative to each other [ 81 83 ]. Climatic warming not only promotes photosynthesis and plant growth but also accelerates the respiration and decomposition of SOM, thus having both positive [ 84 86 ] and negative effects [ 87 89 ] on SOM C stock.…”
Section: Discussionmentioning
confidence: 99%
“…Soil carbon stores have a major impact on global climate change, and LD due to natural conditions or human activities is one of the leading causes of changes in soil carbon storage [78]. In a study conducted in semi-arid steppe areas [79], it was found that a sudden change in soil moisture due to high inter-annual rainfall variability causes about 65-80% of the total carbon loss in soils with different vegetation [80].…”
Section: Soil Organic Mattermentioning
confidence: 99%
“…For example, while an expected 3.3 0 C increase in air temperature will result in a loss of 11-16% SOC in Europe, an average increase of 1°C in surface air temperature will result in a net loss of 5% in the worldwide SOC pool. Temperature increase alone leads to SOC losses in all soil moisture contents [80,83,96,98].…”
Section: Soil Organic Mattermentioning
confidence: 99%